If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + 24(x + -5) = 56x Reorder the terms: 12x + 24(-5 + x) = 56x 12x + (-5 * 24 + x * 24) = 56x 12x + (-120 + 24x) = 56x Reorder the terms: -120 + 12x + 24x = 56x Combine like terms: 12x + 24x = 36x -120 + 36x = 56x Solving -120 + 36x = 56x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-56x' to each side of the equation. -120 + 36x + -56x = 56x + -56x Combine like terms: 36x + -56x = -20x -120 + -20x = 56x + -56x Combine like terms: 56x + -56x = 0 -120 + -20x = 0 Add '120' to each side of the equation. -120 + 120 + -20x = 0 + 120 Combine like terms: -120 + 120 = 0 0 + -20x = 0 + 120 -20x = 0 + 120 Combine like terms: 0 + 120 = 120 -20x = 120 Divide each side by '-20'. x = -6 Simplifying x = -6
| 15=14(y+11) | | .98(x)=18 | | -5c=50 | | 55(8+3)=h | | 4225a+65b+c=310 | | 6=r-70/3 | | (3z+5)+(6z+4)=9z+9 | | 2025a+45b+c=115 | | x^2+3x-(x-4)=28 | | 3/5X15/2= | | y=-7.3x^2+8.25x+2.1 | | 3(4t+32)-8=46 | | 4x+3y+11x-2y= | | 3-3=6x+4x | | 13=10x+30 | | (3(y-2))/5=1-3y | | F=wr | | 6x+2x+x=144 | | 2x/3-x/5=14/15 | | 4w-9w=20 | | (6x-12)(2)=0 | | (6x-12)(2)= | | 2x+10=10x-10 | | 4x^4y^2-6y= | | 7x(2)-3x-5=0 | | 6y/3y | | 3x(x+3)-8=5x-7 | | (4x+50)+(5x+10)=180 | | 3n+6=.18 | | 12x-(2x-8)=58 | | 21+5y=-2y | | 10b^2-(3b^2+6b-8)= |